"A gente chega e invade as quebradas" : identidade social de mulheres MC’S - Luciana Célia da Silva Costa (2016)
This study aims to understand the Social Identity of women MC‟s from the greater Belo Horizonte. MC‟s are RAP songwriters and they are part of the hip-hop movement, which is composed of five elements: the MC, the DJ, graffiti, breakdance and knowledge. Youths in the hip hop movement denounce violence and social exclusion experienced in Brazilian peripheries through artistic, political and social manifestations. This movement is also a space for recovery of black youths, through denunciation and refusal of crime and marginality stigmas associated with these groups. Women represent a numerical minority in the hip-hop and they suffer prejudice against in such context, which makes it difficult for them to be part of it. In order to understand the Social Identities of the women composers in the RAP context, this research aims to answer the following questions based on the Theory of Social Identity: what is it to be an MC composer? How does the fact of being an MC influence the relationship with people in and out of hip-hop? What are the implications in their lives and careers brought up by the fact that they are women songwriters? Therefore, we conducted semi structured interviews with seven women MC‟s in the greater Belo Horizonte. The interviews were recorded and transcribed by the researcher. Moreover, we used the technique called Content Analysis and the NVivo software to examine the data collection, which made it possible to create a grid with the most relevant issues they brought up. This grid worked as a guide for the construction of narratives presented in the outcomes. Hence, it was possible to present common experiences of the interviewees, telling their trajectories. According to the interviewees, being a songwriter is not something given and inalterable because they are constantly changing. Being an MC influences their relationships both in and out of the hip-hop context, and not always they find necessary support. The hip-hop context in which the RAP women songwriters are inserted is still very sexist, which makes it difficult for them to be part of it and develop their careers in the movement. The women MC‟s who are part of the movement have been persisting and battling against many issues, which, between the lines, state that this is not where they should be. However, every time that MC's go up on the stage to sing their songs or battle, they are reaffirming that it is also a place that belongs to them.